Effects of climate on leaf phenolics, insect herbivory, and their relationship in pedunculate oak (Quercus robur) across its geographic range in Europe - Elena Valdés-Correcher; Yasmine Kadiri; Audrey Bourdin; Anna Mrazova; Flavius Bălăcenoiu; Manuela Branco; Michal Bogdziewicz; Mona Chor Bjørn; Thomas Damestoy; Jovan Dobrosavljević; Maria Faticov; Sofia Gripenberg; et al. (Oecologia, 2025)
An increase in biotic interactions towards lower latitudes is one of the most consistent patterns in ecology. Higher temperatures and more stable climatic conditions at low latitudes are thought to enhance biotic interactions, accelerating biological evolution and leading to stronger anti-herbivore defences in plants. However, some studies report contradictory findings, highlighting the need for further investigation into the underlying mechanisms. We used a combination of field observations and feeding trials in controlled environments to investigate the effect of climate on chemical defences and insect herbivory in pedunculate oak ( Quercus robur L.) throughout most of its geographic range in Europe, while controlling for physical defences. The concentration of lignin, flavonoids, and total phenolics increased significantly with temperature, whereas both field herbivory and weight of spongy moth ( Lymantria dispar L.) larvae were negatively influenced by temperature. Lignin concentration positively influenced the weight of spongy moth larvae whereas it had no effect on field herbivory. We found no evidence of strong positive relationships between insect herbivory and larvae growth with leaf defences. Our study underscores the complexity of plant–herbivore interactions along climatic gradients and highlights the need for further research to disentangle these intricate relationships.

Decomposing drivers in avian insectivory: Large‐scale effects of climate, habitat and bird diversity - Laura Schillé; Elena Valdés‐Correcher; Frédéric Archaux; Flavius Bălăcenoiu; Mona Chor Bjørn; Michal Bogdziewicz; Thomas Boivin; Manuela Branco; Thomas Damestoy; Maarten de Groot; Jovan Dobrosavljević; Mihai‐Leonard Duduman; et al. (Journal of Biogeography, 2024)
Aim Climate is a major driver of large‐scale variability in biodiversity, as a likely result of more intense biotic interactions under warmer conditions. This idea fuelled decades of research on plant‐herbivore interactions, but much less is known about higher‐level trophic interactions. We addressed this research gap by characterizing both bird diversity and avian predation along a climatic gradient at the European scale. Location Europe. Taxon Insectivorous birds and pedunculate oaks. Methods We deployed plasticine caterpillars in 138 oak trees in 47 sites along a 19° latitudinal gradient in Europe to quantify bird insectivory through predation attempts. In addition, we used passive acoustic monitoring to (i) characterize the acoustic diversity of surrounding soundscapes; (ii) approximate bird abundance and activity through passive acoustic recordings; and (iii) infer both taxonomic and functional diversity of insectivorous birds from recordings. Results The functional diversity of insectivorous birds increased with warmer climates. Bird predation increased with forest cover and bird acoustic activity but decreased with mean annual temperature and functional richness of insectivorous birds. Contrary to our predictions, climatic clines in bird predation attempts were not directly mediated by changes in insectivorous bird diversity or acoustic activity, but climate and habitat still had independent effects on predation attempts. Main Conclusions Our study supports the hypothesis of an increase in the diversity of insectivorous birds towards warmer climates but refutes the idea that an increase in diversity would lead to more predation and advocates for better accounting for activity and abundance of insectivorous birds when studying the large‐scale variation in insect‐tree interactions.

Changes in the foliar fungal community between oak leaf flushes along a latitudinal gradient in Europe - Álvaro Gaytán; Ahmed Abdelfattah; Maria Faticov; Xoaquín Moreira; Bastien Castagneyrol; Inge Van Halder; Pieter De Frenne; Camille Meeussen; Bart G. H. Timmermans; Jan P. J. G. Ten Hoopen; Pil U. Rasmussen; Nick Bos; et al. (Journal of Biogeography, 2022)
Aim Leaves support a large diversity of fungi, which are known to cause plant diseases, induce plant defences or influence leaf senescence and decomposition. To advance our understanding of how foliar fungal communities are structured and assembled, we assessed to what extent leaf flush and latitude can explain the within‐ and among‐tree variation in foliar fungal communities. Location A latitudinal gradient spanning c . 20 degrees in latitude in Europe. Taxa The foliar fungal community associated with a foundation tree species, the pedunculate oak Quercus robur . Methods We examined the main and interactive effects of leaf flush and latitude on the foliar fungal community by sampling 20 populations of the pedunculate oak Quercus robur across the tree's range. We used the ITS region as a target for characterization of fungal communities using DNA metabarcoding. Results Species composition, but not species richness, differed between leaf flushes. Across the latitudinal gradient, species richness was highest in the central part of the oak's distributional range, and foliar fungal community composition shifted along the latitudinal gradient. Among fungal guilds, the relative abundance of plant pathogens and mycoparasites was lower on the first leaf flush, and the relative abundance of plant pathogens and saprotrophs decreased with latitude. Conclusions Changes in community composition between leaf flushes and along the latitudinal gradient were mostly a result of species turnover. Overall, our findings demonstrate that leaf flush and latitude explain 5%–22% of the small‐ and large‐scale spatial variation in the foliar fungal community on a foundation tree within the temperate region. Using space‐for‐time substitution, we expect that foliar fungal community structure will change with climate warming, with an increase in the abundance of plant pathogens and mycoparasites at higher latitudes, with major consequences for plant health, species interactions and ecosystem dynamics.

Impact of concomitant acid suppressive therapy on pazopanib efficacy and dose reductions in patients with metastatic renal cell carcinoma - Greet Van De Sijpe; Benoit Beuselinck; Tine Van Nieuwenhuyse; Roxanne Poncelet; Oliver Bechter; Maarten Albersen; Eduard Roussel; Marcella Baldewijns; Jan Tack; Isabel Spriet (European Journal of Clinical Pharmacology, 2020)

Postprandial Changes in Solubilizing Capacity of Human Intestinal Fluids for BCS Class II Drugs - Sarah Clarysse; Dimitrios Psachoulias; Joachim Brouwers; Jan Tack; Pieter Annaert; Guus Duchateau; Christos Reppas; Patrick Augustijns (Pharmaceutical Research, 2009)

Parallel Monitoring of Plasma and Intraluminal Drug Concentrations in Man After Oral Administration of Fosamprenavir in the Fasted and Fed State - Joachim Brouwers; Jan Tack; Patrick Augustijns (Pharmaceutical Research, 2007)

P-Glycoprotein Attenuating Effect of Human Intestinal Fluid - Sven Deferme; Jan Tack; Frank Lammert; Patrick Augustijns (Pharmaceutical Research, 2003)